Only God Knows: Maximus the Confessor's Theological Epistemology in the Context of His Revision of the Origenist Myth - Lopez, Eric (Journal of early Christian studies, 2024)
Polycarp Sherwood’s work, The Earlier Ambigua of Saint Maximus the Confessor and his Refutation of Origenism, set the tone for scholarship’s investigation of the terms οὐσία, δύναμις, and ἐνέργɛια in the Confessor’s writings and their use in relation to his late antique context. Since then, scholars have further explored mostly philosophical and some early Christian writings in efforts to locate the usage of the terms amidst changing conceptions of Origenism, Maximus’s relation to Origenism, and expanded studies on their use in philosophical contexts. This study argues that while Maximus was likely aware of many of these philosophical and early Christian writings, the concerns and literature in and around the Council of Constantinople 553 c.e. are the most fitting context for why he chose to develop the sequence. This claim is supported by Maximus’s use of two other terms in his engagement with Origenist doctrines, γνῶσις and ἕνωσις, which also appear in the literature of the 553 Council. A closer look at the terms οὐσία, δύναμις, and ἐνέργɛια highlights a causal relationship that has import for all the ways Maximus employs the terms and puts in relief an irreducible contrast between Creator and creation. Additionally, an investigation into Maximus’s understanding of γνῶσις and ἕνωσις reveals the development of what could be characterized as a divine theological epistemology which functions as another argument supporting the above contrast.